1980
DOI: 10.1063/1.439056
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of the argon⋅acetylene van der Waals molecule

Abstract: Describing van der Waals Interaction in diatomic molecules with generalized gradient approximations: The role of the exchange functional Structure and properties of the argon-ozone van der Waals molecule Radio frequency spectroscopy and Stark effect measurements have been carried out on Ar·HCCH and Ar·DCCD produced in acetylene seeded argon beams. Because of the very small electric dipole moment, Il = 0.02697(3) D, only the 110-111 transition and low frequency pure Stark transitions were observed. Observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…Experimentally, the C 2 H 2 -Ar van der Waals molecular complex has been studied in various spectral regions, including microwave [67][68][69], infrared [56,68,[70][71][72][73][74] and, as already mentioned, near-infrared [39].…”
Section: Argonmentioning
confidence: 99%
“…Experimentally, the C 2 H 2 -Ar van der Waals molecular complex has been studied in various spectral regions, including microwave [67][68][69], infrared [56,68,[70][71][72][73][74] and, as already mentioned, near-infrared [39].…”
Section: Argonmentioning
confidence: 99%
“…Evidence for a low angular anisotropy of the Ar-acetylene interaction was found in Refs. (1) and (3), where expectation values for the angle of 60°and 72°were derived from a D-nuclear quadrupole hyperfine analysis and from the A rotational constant, respectively. The corresponding values for Ar-CO 2 (16), a relatively rigid system, are 81.5°and 84.4°, while the value from a 14 N-nuclear quadrupole hyperfine analysis for the isoelectronic Ar-HCN (17), a highly nonrigid molecule with linear equilibrium geometry, is 59.2°.…”
Section: Table 1 Rotational Transitions Of Ar-acetylene Isotopomersmentioning
confidence: 99%
“…It was first studied by DeLeon and Muenter, using the molecular beam electric resonance technique (1). The J Ka Kc ϭ 1 11 -1 10 transition was measured for both Ar-HCCH and Ar-DCCD.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium structure of the So (1S~) ground state acetylene is linear, whereas that of the first excited singlet state $1 (1/7,) is trans-bent planar [41,42]. The ground state of the acetytene-Ar complex has been studied by molecular-beam electric resonance [44], FT-microwave [45], and IR [46,47] spectroscopy. All these studies have indicated that the complex has a T-shaped, C2~ s~(mmetry, structure with the Ar atom located about 4 A away from the center of mass mum.…”
Section: A Glyoxal Ar Complexesmentioning
confidence: 99%